Cuban Migration and the Sahrawi. Between “Treason” and Hope - Gómez Martín, Carmen (2015)
Despite the scarcity of comparative academic literature, there exists a close relationship between Cuba and the Western Sahara. is connection was carved during the Cold War, by means of the assistance, respect and shared position oered in the face of social emancipation processes. is article reects on the implications of the mobility and migratory control policies of these two experiences that, despite their geographic separation and distinct histories, developed political projects based on the construction of egalitarian societies under the socialist ideology. e established migration discourses and regulations in the two cases show clear connections between both political projects and their steadfastness.